2023
DOI: 10.1111/aji.13679
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of inflammation at the maternal‐fetal interface are altered by SARS‐CoV‐2 infection and pandemic stress

Abstract: Problem:It is now recognized that SARS-CoV-2 infection and pandemic-related stress impacts maternal health. However, their effects at the maternal-fetal interface are still debated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In terms of the COVID‐19 pandemic, the majority of studies have been focused on immunological imbalances that are due to SARS‐CoV‐2 infection itself, without considering the impact of the pandemic and its associated stressors. We and others have shown that SARS‐CoV‐2 infection during pregnancy alters the immune profile at the maternal‐fetal interface 16–20 . Of interest, our team has also reported the impact of pandemic exposure, without SARS‐CoV2 infection, on the placental immune profile, and observed increased lesions and immune cells in the placenta of exposed but uninfected individuals 17,20 .…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…In terms of the COVID‐19 pandemic, the majority of studies have been focused on immunological imbalances that are due to SARS‐CoV‐2 infection itself, without considering the impact of the pandemic and its associated stressors. We and others have shown that SARS‐CoV‐2 infection during pregnancy alters the immune profile at the maternal‐fetal interface 16–20 . Of interest, our team has also reported the impact of pandemic exposure, without SARS‐CoV2 infection, on the placental immune profile, and observed increased lesions and immune cells in the placenta of exposed but uninfected individuals 17,20 .…”
Section: Introductionmentioning
confidence: 73%
“…We and others have shown that SARS-CoV-2 infection during pregnancy alters the immune profile at the maternal-fetal interface. [16][17][18][19][20] Of interest, our team has also reported the impact of pandemic exposure, without SARS-CoV2 infection, on the placental immune profile, and observed increased lesions and immune cells in the placenta of exposed but uninfected individuals. 17,20 Moreover, differences in neurodevelopment at 6 months of age have been reported in babies born during the pandemic without maternal SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Considering the Delta variant, maternal death and preterm birth <37 weeks were, respectively, 0.63% (95% CI, 0.05−1.20%), and 18.58% (95% CI, 9.52−27.65%) [24]. In a previous study of our research group [25] and in some other scientific works [26][27][28][29][30][31][32] Reactive C protein (CRP) serum levels were higher than the normal range, corresponding to a mean value of 56.93 ± 49.57 mg/L. COVID-19 infection in pregnant women seems to negatively affect both maternal and neonatal outcomes.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, pathologic changes in the placenta could represent a prolonged inflammation after virus elimination. Other possibilities are a maternal infection as a trigger for an anti-semi allograft immune reaction of maternal leukocytes against fetal cells within the placenta or a virus-unrelated coincidence [32,45].…”
Section: General Findings In Placentas Of Covid19-pregnanciesmentioning
confidence: 99%